2022
DOI: 10.21203/rs.3.rs-1362548/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synergistic Interactions of Repurposed Drugs that Inhibit Nsp1, a Major Virulence Factor for COVID-19

Abstract: Nsp1 is the first protein expressed from the SARS-CoV-2 genome and is a major virulence factor for COVID -19. A rapid multiplexed assay for detecting the action of Nsp1 was developed in cultured lung cells. The assay is based on the acute cytopathic effects induced by Nsp1. Virtual screening was used to stratify compounds that interact with two functional Nsp1 sites: the RNA-binding groove and C-terminal helix-loop-helix region. Experimental screening focused on compounds that could be readily repurposed to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In SARS-CoV-2, Nsp1 is likely to play many different key roles in the host cell [15]. Other previously published studies have reported that Nsp1 inhibits host protein translation and disrupts the mRNA export machinery to inhibit host gene expression [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In SARS-CoV-2, Nsp1 is likely to play many different key roles in the host cell [15]. Other previously published studies have reported that Nsp1 inhibits host protein translation and disrupts the mRNA export machinery to inhibit host gene expression [16][17][18].…”
Section: Discussionmentioning
confidence: 99%